2023
DOI: 10.1007/s11356-023-25567-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between air pollutants and hospital admissions for chronic obstructive pulmonary disease in Jinan: potential benefits from air quality improvements

Abstract: Evidence between air pollution and chronic obstructive pulmonary disease (COPD) is inconsistent and limited in China. In this study, we aim to examine the associations between air pollutants and hospital admissions for COPD, hoping to provide practical advice for prevention and control of COPD. Hospital admissions for COPD were collected from a Grade-A tertiary hospital in Jinan from 2014 to 2020. A generalized additive model (GAM) was used to examine the associations between air pollutants and hospital admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…We evaluated the optimal df for time with 7, for temperature and relative humidity with 3 to control the long-term and seasonal trends and the effect of temperature and relative humidity. Previous studies showed that the delayed effects of air pollution on COPD morbidity could last for several days, and the biggest air pollution lag effects occur within 7 days [10][11][12]14]. Therefore, we decided to use a maximum lag of 7 days in the DLNM for each pollutant, as in the three documents mentioned above [10][11][12]14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the optimal df for time with 7, for temperature and relative humidity with 3 to control the long-term and seasonal trends and the effect of temperature and relative humidity. Previous studies showed that the delayed effects of air pollution on COPD morbidity could last for several days, and the biggest air pollution lag effects occur within 7 days [10][11][12]14]. Therefore, we decided to use a maximum lag of 7 days in the DLNM for each pollutant, as in the three documents mentioned above [10][11][12]14].…”
Section: Discussionmentioning
confidence: 99%
“…Then the 24 h average concentrations of PM 2.5 , PM 10 , SO 2 , NO 2 , and CO were calculated and represented as daily average concentrations, and the O 3 concentration was an 8 h maximum value concentration (O 3 8h) from all verified monitoring locations. Similar to the methods used in a number of earlier studies [10][11][12]14,15], we calculated the average air pollution concentrations from the 2 monitoring sites to represent the overall exposure for all people. Daily meteorological information, which comprised temperature and relative humidity, was supplied by the China Meteorological Data Service Center (http://data.cma.cn/, accessed on 12 March 2020).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 20-40% of all AECOPD events are triggered by non-infectious conditions, such as cardiovascular comorbidities (in particular heart failure), pulmonary embolisms, extra-pulmonary infections, and pneumothorax [63]. Moreover, some precipitating factors of AECOPD could also be represented by air pollution and/or cold air exposure, allergen exposure, tobacco smoking, and, not negligibly, a poor adherence with COPD therapies, including oxygen [64][65][66][67]. Interactions between all the possible triggers (the pathogens, indoor and outdoor pollution) and a patient's characteristics increase the inflammation in the lower airways, leading to tissue damage.…”
Section: Risk Factors For Aecopd Requiring Icumentioning
confidence: 99%
“…Air pollution is a substantial environmental issue with profound implications for public wellbeing, particularly respiratory health. Industrial air pollution is a significant concern, with numerous studies highlighting its adverse effects on respiratory health [1][2][3]. Industrial activities, such as the combustion of fossil fuels, emit a wide range of pollutants, among which fine particulate matter (PM2.5) is prominent.…”
mentioning
confidence: 99%